Comparison of Vitamin C Content in Fresh and Canned Mandarin Oranges (Citrus reticulata Blanco) at a Supermarket in Pontianak - Erwansani, Enggy; Reynaldi, Muhammad Andre; Evifani, Dinda Silvia; Fong, Siau; Fendi, Fendi; Stevia, Tessa; Saputra, Rico; Setiawansyah, Arif (Journal of Food and Pharmaceutical Sciences, 2025)
Abstract: Vitamin C is one of the micronutrients needed and cannot be synthesized by the human body so it needs intake from the outside such as fruits. Mandarin oranges are one of the sources of vitamin C that is widely circulated in Pontianak City. This fruit can be available in both fresh and canned form. However, the heating process during the processing of canned fruit can damage the vitamin C content in it. Therefore, an analysis is needed to compare vitamin C levels in fresh and canned mandarin fruits. The methods used were in the form of tube tests using FeCl3, KMnO4, and I2, as well as quantitative tests using uv-vis spectrophotometry. The results showed that the two positive samples contained vitamin C with a level of 78.56912152 mg/100 g in the fresh sample and 31.95655685 mg/100 g in the canned sample. Thus, it can be concluded that the vitamin C level in fresh mandarin oranges is higher than in canned mandarin oranges.